Influence on the adult male Leydig cell biomarker insulin‐like peptide 3 of maternal exposure to estrogenic and anti‐androgenic endocrine disrupting compound mixtures: A retrospective study. (19th August 2022) - Ivell, Richard; Vinggaard, Anne Marie; Soyama, Hiroaki; Anand‐Ivell, Ravinder
Abstract: Insulin‐like peptide 3 (INSL3) is a peptide biomarker secreted specifically by the mature Leydig cells of the testes. It is constitutive, has low within‐individual variance, and effectively measures the functional capacity of Leydig cells to make testosterone. In young adult men there is a large 10‐fold range of serum INSL3 concentration, persisting into old age, and implying that later hypogonadal status might be programmed in early life. To determine whether maternal exposure to environmental endocrine disrupting compounds (EDCs) influences adult serum INSL3 concentration, using a retrospective paradigm, INSL3 was measured in young adult male rats (80–90 days) from the F1 generation of females maternally exposed to varied doses of bisphenol A (BPA), butylparaben, epoxiconazole, and fludioxonil as single compounds, as well as estrogenic and anti‐androgenic mixtures of BPA and butylparaben, and di(2‐ethylhexyl) phthalate and procymidone respectively. A mixture of BPA and butylparaben significantly reduced circulating INSL3 concentration in adult male progeny. The remaining compounds or mixtures tested, though sufficient to induce other effects in the F1 generation were without significant effect. Maternal exposure to low concentrations of some EDCs may be a contributing factor to the variation in the Leydig cell biomarker INSL3 in young adulthood, though caution is warranted translating results from rats to humans.